The challenge of translating children's literature - Kaloh Vid, Natalia (ELOPE (Ljubljana), 2008)
In the article the author focuses on Vladimir Nabokov's translation of Lewis Carroll's novel Alice's Adventures in Wonderland, made in 1923. The main intention of the article is to analyze Nabokov's translation strategies of domestication, realized in the text as substitution and localization, and to explain possible reasons for his decision in favour of almost complete Russification of the original. It is possible that Nabokov considered children's attitude towards the final result as the most important part of the translation process. Thus, he used domesticated strategies to transfer for Russian children the humour, the originality and brightness of the paradoxical and attractive world of Lewis Carroll, his sense of the absurd and his amazing gift for games of logic and language, providing a recognizable and familiar atmosphere for the readers. Undoubtedly, his young Russian readers were able to identity themselves with the story and to comprehend the complex world created by Lewis Carroll. On the other hand, Nabokov refuses to oversimplify his translation or to patronize its young audience through simplistic translation solutions.
Keywords: children's literature; domesticated translation; književni prevodi; literary translation; otroška književnost; prevajanje; translation